The effects of text messaging for promoting the retention of the first-time blood donors, a randomized controlled study (TEXT study) - Chontara Pongsananurak (2020)
© 2020 AABB Background: Donor recruiting remains a challenging process to obtain sufficient blood product supply worldwide. This was a randomized controlled trial aimed to evaluate the efficacy of text messaging for promoting the retention of first-time blood donors. Study Design and Methods: Participants enrolled were 18 years of age or older who were first-time blood donors and able to understand text messages. Participants were randomized in a 1:1 ratio (text group vs control group). Only participants who were allocated in the “text group” received a text message once their blood product was dispatched from the transfusion service. The content of the text message was “We would like to inform you that your blood has been used for patients on the date (DD/MM/YY).” The primary outcome of the study was the rate of returning at 9 months after the first donation. Results: In an intention-to-treat analysis, 1270 participants were allocated to the text group and 1270 participants to the control group. The primary outcome occurred in 199 in the text group (22.4 per 100 donor-years) and 152 in the control group (16.9 per 100 donor-years). The incidence rate ratio was 1.31 (95% confidence interval, 1.06-1.63; P =.005). The number needed to treat was 22. The median time to return for blood donation was 112 days (interquartile range [IQR], 98-146) in the text group and 113 days (IQR, 97-144) in the control group. Conclusion: Among first-time blood donors, text messaging after blood product being dispatched is an effective and simple intervention to increase the retention rate for subsequent donations.